A Cultural Impact of Television Network in the Core of Social Transformation and Development: Examining the Cultural Impacts of Television Networks on Social Transformation and Development (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the core of present entertainment scenario, television has occupied an essential factor position in every household. The several experiments, manual modifications and applicable methods have been changed from generation to generation for the technical touch usage television networks. Because of these television networks a huge habitat also been altered in internal and external life Especially in social transformation and development, majority of the people has become change and exchange their food trend, dress code, language communication and lifestyle at multi stage cultural dimension in the name of western imitations as well as excitements. Hence the moral based television network introduces the mankind culture towards canalizes the valuable development. In that same way TV classifies the cultural development from very past to present, As well it communicates, relates and correlates all over the world. Even technical change modification of television network are never ending forever While discussing this coverage, the study has framed a couple of objectives ‘study the cultural impacts of television networks for social transformation and development in universal manner’ and ‘identify the top most five Hindi televisions shows in India’. A few hypotheses are too set for the study to meet the objectives ‘significantly television networks culturally impacts much in several dimensions for social transformation and development activities’ and ‘significantly talent and cricket oriented shows occupied a top most position at Hindi televisions shows in India’. Hence this paper carried both primary and secondary data. The primary data represents the author’s views, thoughts and present ideal issues on the topic. As well secondary data has been gathered from the published articles, books, literatures and reports on the subject. Finally, the passage discussed about the trends, conditions, several pictures and updates of television network under cultural impacts in the way of social transformation and development.